Guidelines for Prevention and Suppression of Motorcycle Theft in the area of Responsibility of Muang Nakhon Pathom Police Station - Klinbubpa, Chaiyarith (Arts of Management Journal, 2020)
The purposes of this research were to study the problems and forms of motorcycle theft in the area of Muang Nakhon Pathom Provincial Police Station and seeking for the approaches in the prevention of motorcycle theft that are suitable for the circumstances in the area of responsibility of Muang Nakhon Pathom Provincial Police Station. This study was a qualitative research. The researcher conducted in-depth interviews with 10 commissioned police officers and noncommissioned police officers of Muang Nakhon Pathom Police Station and 5 police officers of Nakhon Pathom Provincial Police Investigation Division. Research instruments of the study were in-depth interviews, questionnaires, and specific selection criteria. A statistic used was descriptive content analysis. The results of the study revealed that 1) There was a large number of stolen motorcycles with a tendency of increasing violence in each year, which was the problem of motorcycle theft in the area of responsibility of Muang Nakhon Pathom Provincial Police Station. There were two forms of theft: people are careless and the motorcycle theft process uses special tools for theft. The area where motorcycles are most stolen are dormitories and rental rooms. The most stolen motorcycle time was at night. 2) Guidelines for the prevention and suppression of motorcycle theft of Nakhon Pathom Provincial Police Station, including establishing checkpoints when suspicious motorcycles are found, call for inquiries and history theft of information is kept in every case, separated into files. There is hope for the person who committed the case of stealing a motorcycle that was released from punishment.